Pengaruh Tingkat Pendidikan terhadap Kinerja Kepala Desa - Cici Paramida Situmorang; Irwan Nasution; Yurial Arief Lubis (Universitas Medan Area, 2021)
methods). So in this study the authors used a combination sequential explanatory design method. In the quantitative method the independent variable in this study is the level of education, while the dependent variable is the performance of the village head. This research is a survey research. The sample used in this study was 19 respondents who worked as village heads who were determined by using sampling techniques for specific purposes (purposive sampling). Data analysis using correlation techniques to determine the effect of the independent and dependent variables partially used t test. Meanwhile, to determine the effect of the independent and dependent variables simultaneously, the F test is used. The results of this study indicate that with a significant level of p = 0.05 simultaneously and partially the level of education variable affects the performance of the Village Head in Pantai Labu District, Deli Serdang Regency. Whereas in the Qualitative Method, the Data Collection Technique using the Interview Technique, which will then make a comparison between Quantitative and Qualitative Data Analysis, whether there are differences or even similarities.